Developing Regional Market Based on Local Commodity: (Case Study on Regional Market in Pasuruan Regency) - Handayati, P (KnE Social Sciences, 2018)
The term of ”folk market” is used to indicate where local trade takes place, thus containing indigenous traits that have been going on for a very long time. Focal point of the folk market can be observed from its influence on the fulfillment of the livelihood of small communities. That is why the folk market can be a pillar of people’s economy. The purpose of this study is to formulate the strategy of development of Regional Market in Pasuruan to improve the economy of the community. The result of internal factor analysis hence can be known that some factor become strength and weakness of traditional market in Pasuruan regency. The most prominent strength factor is that all markets sampled in this study lie in a strategic location. This means that the community is quite easy to reach the market location, because it is attached to public transportation. In addition, the market location is not located in areas prone to disasters, such as floods or landslides. As for the most prominent weakness factors, the existence of inadequate sanitation. The regional government of Pasuruan Regency needs to revitalize the traditional market, which is the improvement (renovation) of the physical building of the market and is accompanied by institutional building such as developing organizational development of traditional market managers and builders, including the development of market management system along with human resources (SDM) involved and market traders..To improve the marketing of local products of Pasuruan regency, it can be done through: providing adequate parking and loading facilities, provide special agricultural storage facilities, improve hygiene, because superior local agricultural products with premium quality requires post-harvest handling and good storage techniques, building adequate mechanical electric facilities and enabling market participants to operate cooling machines to maintain product quality, organize superior product displays to make them more attractive, complete facilities, promotion of informative products, enhancing the ability of market participants to understand the principles of serviceoriented consumer satisfaction. Keywords: Regional Market, Superior Product